Variation in Manduca sexta Pollination-Related Floral Traits and Reproduction in a Wild Tobacco Plant - Bing, Julia; Li, Xiang; Haverkamp, Alexander; Baldwin, Ian T.; Hansson, Bill S.; Knaden, Markus; Yon, Felipe (Frontiers in Ecology and Evolution, 2021)
Most flowering plants depend on animal pollination for successful sexual reproduction. Floral signals such as color, shape and odor are crucial in establishing this (often mutualistic) interaction. Plant and pollinator phenotypes can vary temporally but also spatially, thus creating mosaic-like patterns of local adaptations. Here, we investigated natural variation in floral morphology, flower volatile emission and phenology in four accessions of a self-compatible wild tobacco, Nicotiana attenuata, to assess how these traits match the sensory perception of a known pollinator, the hawkmoth Manduca sexta. These accessions differ in floral traits but also in their habitat altitudes. Based on habitat temperatures, the accession occurring at the highest altitude (California) is less likely to be visited by M. sexta, while the others (Arizona, Utah 1 and Utah 2) are known to receive M. sexta pollinations. The accessions varied significantly in flower morphologies, volatile emissions, flower opening and phenology, traits likely important for M. sexta perception and floral handling. In wind tunnel assays we assessed seed-set of emasculated flowers after M. sexta visitation and of natural selfed and hand-pollinated selfed flowers. After moth visitations, plants of two accessions (Arizona and Utah 2) produced more capsules than the other two, consistent with predictions that accessions co-occuring with M. sexta would benefit more from this moth’s pollination services. We quantified flower and capsule production in four accessions in a glasshouse assay without pollinators to assess the potential for self-pollination. The two Utah accessions set significantly more seeds after pollen supplementation compared to those of autonomous selfing flowers, suggesting a greater opportunistic benefit from efficient pollinators than the other two. Moreover, emasculated flowers of the accession with the most exposed stigma (Utah 2) produced the greatest seed set after M. sexta visitation. This study reveals intraspecific variation in pollination syndromes that illuminate the potential of a plant species to adapt to local pollinator communities, changing environments and altered pollination networks.